Bioadsorption of Heavy Metals From Industrial Wastewater Using Some Species of Bacteria (Baghdad Science Journal, 2016)
Three isolated bacteria were examined to remove heavy metals from the industrial wastewater of the Diala State Company of Electrical Industries, Diyala-Iraq. The isolated bacteria were identified as Pseudomonas aeruginosa, Escherichia coli and Sulfate Reducing Bacteria (SRB). The three isolates were used as an adsorption factor for different concentrations of Lead and Copper (100, 150, and 200 ppm.), in order to examine the adsorption efficiency of these isolates. In addition, the effect of three factors on heavy metals adsorption were examined; temperature (25, 30, and 37 ?C), pH (3 and 4.5) and contact time (2 and 24 hrs). The results showed that the highest level of lead adsorption was obtained at 37 ?C by E. coli, P, aerugenosa and SRB with percentage of 95, 95.3 and 99.7 % respectively, whereas, E. coli, P. Aerugenosa and SRB gave a copper adsorption percentage of (40.63, 50.51 and 80.57%) respectively at 37 ?C. Moreover, E.coli showed different percentage of metal adsorption ranged from 6.4% to 95 % with lead concentration of 100 and 200 ppm at pH4.5 and for each of 2 and 24 hrs contact time, whereas, it exerts percentage of copper adsorption ranged from 3.5 % to 40.63 % at 100 and 200 ppm and pH value of 4.5 for similar contact time. P. aerugenosa was also shown to be involved in metal adsorption with percentage ranged from 1.39 % for lead concentration of 150 ppm to 97.9 % for 200ppm under pH of 3 and contact times of 2 and 24 hrs. Interestingly, SRB exhibits significant differences in metal absorption values ranged from 14.97 % for lead (100 ppm) to 99.32 % at 200 ppm with a pH value of 3 and contact times of 2 and 24 hrs and under different temperatures.